Adorno et Althusser, lecteurs de Hegel - Jean-Baptiste Vuillerod (Astérion)
This article aims to reconcile Louis Althusser and Theodor W. Adorno’s philosophies by confronting them with three questions that they raised: the primacy of theory, the theory of society and history, the criticism of the notion of subject. In each case, the issue is to stress the common features of their thoughts but also to emphasize their difference of opinion about Hegel’s philosophy. If Althusser is about searching for a non-Hegelian Marxism, on the contrary Adorno deals with a new reading of Hegel to rethink Marxism in a time of crisis.